Functional denture soft liner with antimicrobial and antibiofilm properties - Tuba Baygar; Aysel Ugur; Nurdan Sarac; Uydu Balci; Gulfem Ergun (Elsevier, 2018)
Background/purpose: Denture soft liners, especially used for elders who have poor disinfection habits, provide a favourable environment for accumulation and colonization of microorganisms. This in vitro study is aimed to investigate the effectiveness of natural carvacrol incorporation into soft lining material on the inhibition of oral pathogens. Materials and methods: Antimicrobial susceptibility of carvacrol was primarily determined by disc diffusion method. Soft lining material was prepared as recommended by the manufacturer and 10 μL carvacrol was added aseptically to the soft liner discs. Inhibition zones for the control discs without carvacrol (C) and carvacrol-incorporated discs (CL) were determined by disc diffusion method. The biofilm inhibition percentages of carvacrol on soft liner was determined by MTT assay and also observed by Scanning Electron Microscopy (SEM). Results: Carvacrol displayed great antimicrobial activity for yeast, Gram-negative and Gram-positive strains. The highest inhibition zone of carvacrol (41.33 ± 1.53 mm) was measured for Bacillus subtilis strain which is followed by Candida albicans and Streptococcus sanguis (34.00 ± 1.73 mm and 32.33 ± 0.58 mm, respectively). The inhibition zones were also similar for soft liner discs with carvacrol, with the highest inhibition zones against B. subtilis, Streptococcus mutans and C. albicans (43.67 ± 0.58 mm, 40.33 ± 0.58 mm and 38.33 ± 1.15 mm, respectively). Incorporation of carvacrol into the soft liner decreased (98.03 ± 0.2%) of the biofilm formation for C. albicans. Conclusion: Carvacrol-incorporation obviously decreased the colonization and plaque formation of oral pathogens, especially C. albicans accumulation. Carvacrol may be useful as a promising agent for antibacterial and antifungal management for denture soft lining materials. Keywords: antibacterial, antibiofilm, antifungal, carvacrol, soft liner